SPEC HPG benchmarks for high-performance systems. (23rd January 2006) - Muller, Matthias S.; Kalyanasundaram, Kumaran; Gaertner, Greg; Jones, Wesley; Eigenmann, Rudolf; Lieberman, Ron; Waveren, Matthijs; Whitney, Brian
In this paper, we discuss the results and characteristics of the benchmark suites maintained by the Standard Performance Evaluation Corporation's (SPEC) High-Performance Group (HPG). Currently, SPECHPGhas two lines of benchmark suites for measuring performance of large-scale systems SPEC OMP and SPEC HPC2002. SPEC OMP uses the OpenMP API and includes benchmark suites intended for measuring performance of modern shared memory parallel systems. SPEC HPC2002 uses both OpenMP and MPI, and thus it is suitable for distributed memory systems, shared memory systems and hybrid systems. SPEC HPC2002 contains benchmarks from three popular application areas: chemistry, seismic and weather forecasting. Each of the three benchmarks in HPC2002 has a small and a medium data set in order to satisfy the need for benchmarking a wide range of high-performance systems. We analyse published results of these benchmark suites regarding scalability. We also present current efforts of SPEC HPG to create new releases of the benchmark suites.